The Association between Neighborhood Disorder and Health: Exploring the Moderating Role of Genotype and Marriage - Lei, Man-Kit (Int J Environ Res Public Health, 2021)
The present study extends prior research on the link between neighborhood disorder and health by testing an integrated model that combines various social and biological factors. Hypotheses were tested using a sample of 325 African American women from the Family and Community Health Study (FACHS). As expected, inflammatory burden was the biophysiological mechanism that mediated much of the association between neighborhood physical disorder and perceived physical health. This finding provided additional support for the view that global self-ratings of health are powerful predictors of morbidity because, in large measure, they are indicators of chronic, systemic inflammation. Further, both genetic variation and marital status served to moderate the association between neighborhood disorder and health. Finally, being married largely eliminated the probability that neighborhood disorder would combine with genetic vulnerability to increase inflammatory burden and perceived illness. Overall, the findings demonstrate the value of constructing integrated models that specify various biophysiological mechanisms that link social conditions to physical health.